The Production of Clitic Pronouns: A Study on Bilingual and Monolingual Dyslexic Children - Vender, Maria; Hu, Shenai; Mantione, Federica; Delfitto, Denis; Melloni, Chiara (Frontiers in Psychology, 2018)
Clitic production is reported to be challenging for impaired children, suffering from dyslexia or SLI, and for early second language learners too. On the contrary, research has not directly investigated the relation between dyslexia, bilingualism and clitic production. Our study aims at addressing this issue, by comparing the performance of 4 groups of children in a clitic elicitation task: 25 Italian monolingual dyslexic children (mean age 10;08 years old), 33 Italian monolingual typically developing children (9;99 y.o.), 25 bilingual dyslexic children with Italian as L2 (10;31 y.o.) and 31 bilingual typically developing children with Italian as L2 (10;30 y.o.). As inclusion criteria, bilingual children had at least 5 years of exposure to Italian, including 3 years of consecutive school attendance in Italy. Clitic production was assessed by means of an elicitation task in which the pronoun had to be produced either in the simple present or in the present perfect; higher difficulties were expected in this last condition, in which the clitic has to agree in gender and number with the past participle. Results revealed that dyslexic children, both monolingual and bilingual, performed worse than controls both in the simple present and in the present perfect condition, indicating that clitic production is challenging in dyslexia. As for the bilingual children, instead, differences were found between the two conditions. In the simple present, bilingual children performed very accurately and similarly to their monolingual peers, indicated that a target performance with clitics is accomplished by typically developing children with a longer exposure to Italian and suggesting that previously reported difficulties were related to linguistic immaturity and are likely to disappear as their L2 exposure and competence grow. In the present perfect, instead, both groups of bilinguals performed worse than their monolingual peers, suggesting that bilingualism could exacerbate the difficulties in the most challenging condition. Importantly, however, no negative effect of bilingualism in clitic production was found once controlling for the subjects’ vocabulary, evidencing the importance of lexical competence in the target language for a native-like performance in clitic production.